Assessment of Brushing Techniques in School Children and Its Association with Dental Caries, Omdurman, 2019 - Rugaia Eltayeb Hag Maki Ibrahim; Maha O. Helaly; Ehab Mohamed Abdelhlim Ahmed (International Journal of Dentistry)
Background. Dental caries are a common infectious disease of childhood. It is a highly prevalent disease among children. Aim. The goal of this study was to assess the different brushing techniques used by school children and to identify if there is an association between brushing techniques and dental caries. Materials and Methods. A descriptive cross-sectional study was carried out among 396 school children (9–12 years old) chosen by convenience sampling technique from schools located in Omdurman locality, Sudan. After consent was taken, students were asked in an interview-based questionnaire about their brushing habits. Consequently, they were examined in an upright position using a sterile mouth mirror and a probe. The examination was carried out by a single examiner to investigate the presence of dental caries. The diagnosis was done based on the World Health Organization diagnostic criteria 2013. The data were analyzed through descriptive statistics and comparison between values using the chi-square test with a P value <0.05. Results. The present study found that the prevalence of dental caries is 70.9%. The combined brushing technique was the most used technique (42.9%). There was no statistical significance between brushing techniques and dental caries (P value ≤0.330). There was a statistical significance between the periodic change of the toothbrush and dental caries (P value ≤0.001). There was statistical significance between the level of education of the mother (P value ≤0.001) and father (P value ≤0.012) to the brushing technique used by the child as well. Conclusion. Due to a lack of awareness consequent of lower socioeconomic status, only a few percentage of the Sudanese population knows how to implement the correct oral hygiene practices to combat dental caries. It is important to design a specific public health program that particularly targets families of low socioeconomic status, which represents the majority. Dental caries persist as a widespread condition in Sudan as a result of a deficit in these kinds of programs.